Pengaruh Kepuasan Kerja dan Komitmen Organisasi Afektif Terhadap Job Performance pada PTSP di Kementerian Kabupaten Semarang - Damyani, Deis Anggit; Dwi Putranti, Honorata Ratnawati (Transformasi: Journal of Economics and Business Management, 2025)
This study aims to analyze the effect of job satisfaction and affective organizational commitment on job performance at PTSP in the Ministry of Religious Affairs of Semarang Regency. Job satisfaction reflects employees' positive feelings towards their work, while affective organizational commitment reflects employees' emotional attachment to the organization. Both of these factors are believed to play an important role in improving job performance, especially in the public service sector. This study uses a quantitative method with multiple linear regression analysis techniques. Data were collected through questionnaires distributed to 60 PTSP employees as respondents. The results of the analysis show that job satisfaction has a positive and significant effect on job performance, which means that the higher the job satisfaction, the better the job performance. In addition, affective organizational commitment also has a positive and significant effect on job performance, indicating that employees with high emotional commitment to the organization tend to be more productive and dedicated. These findings confirm that increasing job satisfaction and affective organizational commitment can be an effective strategy in improving job performance in the public service sector. Therefore, organizations are advised to create a work environment that supports and strengthens employees' emotional ties to the organization.